Tracking of Axonal Bundles in Diffusion MRI Brain Images - Piskořová, Z. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The aim of this work is to design tracking algorithm which will be able to track brain axonal bundles in diffusion weighted MRI data. Estimation of anisotropic diffusion profile inside voxels was performed by diffusion tensor imaging model (DTI). Tracing is based on the 4th order Runge-Kutta method. Algorithm is implemented in the MATLAB computing environment and is tested on real data biological phantom.
Keywords: Diffusion MRI; tractography; diffusion tensor imaging; DTI; Runge-Kutta method; deterministic tracking algorithm